2005
DOI: 10.1507/endocrj.52.111
|View full text |Cite
|
Sign up to set email alerts
|

3β-Hydroxysteroid Dehydrogenase in Human Aorta

Abstract: Abstract. 3b-hydroxysteroid dehydrogenase (3b-HSD) is known to be involved in steroid production and/or metabolism and to be expressed in many tissues including adrenal cortex. Expression of this enzyme has also been elucidated in human cardiovascular system but its details remain largely unknown. Therefore, in this study, we examined the status of 3b-HSD in postmortem human aorta utilizing RT-PCR and immunohistochemical analysis. Both mRNAs and immunoreactivity for the enzyme were detected predominantly in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Our data show that primary HBVSMC express the gonadal steroid receptors AR, ERα, ERβ, as well as enzymes involved in 3β-diol metabolism. This is consistent with previous studies showing that blood vessels contain AR, ERα, ERβ, and 3β-HSD [24-27,29,30]. Additionally, we found that AR and ERβ mRNA expression was not altered by cytokine treatment in our human cell model.…”
Section: Discussionsupporting
confidence: 93%
“…Our data show that primary HBVSMC express the gonadal steroid receptors AR, ERα, ERβ, as well as enzymes involved in 3β-diol metabolism. This is consistent with previous studies showing that blood vessels contain AR, ERα, ERβ, and 3β-HSD [24-27,29,30]. Additionally, we found that AR and ERβ mRNA expression was not altered by cytokine treatment in our human cell model.…”
Section: Discussionsupporting
confidence: 93%
“…A third and less explored pathway for androgen action is through the conversion of DHT to 3␤-diol, an ER␤ agonist (21,22,47), by the enzymes 3␤-hydroxysteroid dehydrogenase (3␤-HSD), 3␣-hydroxysteroid dehydrogenase (3␣-HSD) and 17␤-hydroxysteroid dehydrogenase (17␤-HSD) (12,19,41,44,47). Blood vessels contain AR, ER␣, ER␤, 5␣-reductase, aromatase, and 3␤-HSD (13,30,38,39); therefore, the presence of these enzymes and receptors allows for potential androgenic and estrogenic effects that can influence vascular inflammation through a variety of pathways. Our current data point to ER␤ as a possible alternative receptor pathway for the action of DHT during pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining procedure and characterization of primary antibodies used in the preset study have been described previously [5][6][7].…”
Section: Immunohistochemistrymentioning
confidence: 99%